Bipolar Disorder and Outcomes of Monotherapy with Lithium, Valproate, Quetiapine, Olanzapine, Venlafaxine, and Citalopram - Bohlken, Jens; Riedel-Heller, Steffi; Bauer, Michael; Kostev, Karel (Pharmacopsychiatry, 2021)
Introduction The aim of this study was to compare the outcomes of monotherapy in individuals with bipolar disorder who are prescribed lithium, valproate, quetiapine, olanzapine, venlafaxine, or citalopram in private psychiatric practices in Germany.Methods This retrospective study included bipolar disorder patients who had initially started on a monotherapy with lithium, valproate, quetiapine, olanzapine, venlafaxine, or citalopram in 93 private neuropsychiatric practices in Germany between January 2006 and December 2017. Treatment failure was defined as time to discontinuation of medication or addition of another mood stabilizer, antipsychotic, antidepressant, or benzodiazepine.Results A total of 4990 bipolar patients was examined for the period between 2006 and 2019. Initially, monotherapy with lithium (n=1.098), valproate (n=502), quetiapine (n=927), olanzapine (n=927), venlafaxine (n=574), or citalopram (n=962) was prescribed. Within 24 months, treatment failure had occurred in 76.3% (lithium), 85.1% (valproate), 84.6% (quetiapine), 85.2% (venlafaxine), 92.1% (olanzapine), and 86.6% (citalopram) of patients, respectively. The hazard ratio for treatment failure compared to lithium as reference was highest for olanzapine at 1.66 (1.46–1.88), followed by citalopram 1.27 (1.15–1.39), quetiapine 1.18 (1.07–1.29), valproate 1.18 (1.06–1.33), and venlafaxine 1.14 (1.02–1.27).Conclusions Our results underline the importance of lithium in the maintenance treatment of bipolar disorders.
Keywords: bipolar disorders; lithium; valproate; quetiapine; olanzapine; venlafaxine